2021
DOI: 10.1038/s41598-021-83468-7
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and electronic topological transition of hydrogen-rich metal Li5MoH11 under high pressures from first-principles predictions

Abstract: Regarded as doped binary hydrides, ternary hydrides have recently become the subject of investigation since they are deemed to be metallic under pressure and possibly potentially high-temperature superconductors. Herein, the candidate structure of Li5MoH11 is predicted by exploiting the evolutionary searching. Its high-pressure phase adopts a hexagonal structure with P63/mcm space group. We used first-principles calculations including the zero-point energy to investigate the structures up to 200 GPa and found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The possibility of finding an electron in the neighboring space of HfO 2 can be measured by the electron localization function (ELF) [41], as reported in Figure 2, where the structure of HfO 2 is presented as shown in Figure 2 (a). The tendency of ELF in HfO 2 is described by the uniform distribution of electron gas with the same density [31,32,42,43,44,45,46]. For the P4/nmm structure, the calculated ELF reveals a set of chemical bonding at the pressure of 150 GPa.…”
Section: Resultsmentioning
confidence: 92%
“…The possibility of finding an electron in the neighboring space of HfO 2 can be measured by the electron localization function (ELF) [41], as reported in Figure 2, where the structure of HfO 2 is presented as shown in Figure 2 (a). The tendency of ELF in HfO 2 is described by the uniform distribution of electron gas with the same density [31,32,42,43,44,45,46]. For the P4/nmm structure, the calculated ELF reveals a set of chemical bonding at the pressure of 150 GPa.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, Li 2 MgH 16 shows a superhigh T c up to 430–473 K with extremely strong electron–phonon coupling ( λ = 4) at 250 GPa, in which half of total λ is contributed by the bending modes of atomic H 42 . In contrast, the high‐pressure phase of Li 5 MoH 11 with P 6 3 / mcm symmetry, consisting of face‐shared MoH 12 icosahedra and vertex‐shared HLi 5 trigonal bipyramids, has a weak EPC‐induced T c of 6.5 K at 160 GPa due to low DOS at the Fermi level and the isolated H atoms (the nearest H–H distance is larger than 1.44 Å) 66,111 …”
Section: Sths With Metalmentioning
confidence: 99%
“…110 Therefore, Li 2 MgH 16 shows a superhigh T c up to 430-473 K with extremely strong electron-phonon coupling (λ = 4) at 250 GPa, in which half of total λ is contributed by the bending modes of atomic H. 42 In contrast, the high-pressure phase of Li 5 MoH 11 with P6 3 /mcm symmetry, consisting of faceshared MoH 12 icosahedra and vertex-shared HLi 5 trigonal bipyramids, has a weak EPC-induced T c of 6.5 K at 160 GPa due to low DOS at the Fermi level and the isolated H atoms (the nearest H-H distance is larger than 1.44 Å). 66,111 On the other hand, Mg can also form H-rich STHs with other metal elements such as Pm-3 MgGeH 6 for Ge and Pmn2 1 MgVH 6 for V, respectively. MgGeH 6 (Figure 5b), lying on the convex hull at 200-300 GPa, shows H-dominated metallicity and significant "flat band-steep band" feature near the Fermi level, leading to strong EPC with 50% from H-derived high frequency.…”
Section: Bimetal Sthsmentioning
confidence: 99%
“…Furthermore, it is well known that a trustworthy criterion to reach a high T c in hydride materials is a specific combination of strong covalent bonding between hydrogen and other elements of the compound, and the presence of high-frequency modes in the phonon spectrum [7]. On that wise, theoretical calculations have allowed the prediction of the electronic, dynamic and electronphonon (el-ph) coupling properties of hydrogen-rich compounds at high pressures; leading to promising SC systems with T c near room temperature [8][9][10][11][12][13][14]. One of them concluded that in the observed T c evolution as a function of pressure, the role of the energy-dependence on the density of states at the Fermi level, N (0), is crucial for the proper analysis and description of the superconducting state on high-T c metal hydrides as H 3 S, by considering its van Hove singularities [8].…”
Section: Introductionmentioning
confidence: 99%